2020
DOI: 10.1111/rec.13192
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in vegetation and seed bank composition highlight the importance of post‐restoration management in sown grasslands

Abstract: Sowing grasses supports the rapid development of a closed perennial vegetation, which makes the method universally suitable for fast and effective landscape-scale restoration of grasslands. However, to increase their diversity and to create a natural-like species-rich grassland is a challenging task. Understanding the role of seed bank compositional changes and vegetation dynamics can help to design management regimes that support the establishment of target species and suppress unwanted weeds. Our aim was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…Key issues explored in the Special Issue include grazing (Blackburn et al 2021 b ), fire, mowing, land‐use legacies (nitrogen deposition, weed invasion), soil seed banks (Valkó et al 2021), and abandonment of disturbance (Hernandez et al 2021; Price et al 2021; Reis et al 2021; Valkó et al 2021; Blackburn et al 2021 b ). Although restored grasslands have a disturbance requirement, optimal management may differ in restored grasslands from reference sites due to differences in species composition, land‐use legacies, weed invasions, or other factors.…”
Section: Disturbance and Land‐use Legacies In Restorationmentioning
confidence: 99%
See 3 more Smart Citations
“…Key issues explored in the Special Issue include grazing (Blackburn et al 2021 b ), fire, mowing, land‐use legacies (nitrogen deposition, weed invasion), soil seed banks (Valkó et al 2021), and abandonment of disturbance (Hernandez et al 2021; Price et al 2021; Reis et al 2021; Valkó et al 2021; Blackburn et al 2021 b ). Although restored grasslands have a disturbance requirement, optimal management may differ in restored grasslands from reference sites due to differences in species composition, land‐use legacies, weed invasions, or other factors.…”
Section: Disturbance and Land‐use Legacies In Restorationmentioning
confidence: 99%
“…Here, the optimal management to reduce exotics and increase native richness was hoeing, and though other techniques reduced exotic cover, they did not meet the restoration goal of also increasing native species richness and cover. In restored grasslands, Valkó et al (2021) demonstrated that ongoing disturbance management was needed to maintain cover of sown target species and reduce weeds. Here, remnant grasslands were less dependent on management, confirming differences in restored compared to remnant sites.…”
Section: Disturbance and Land‐use Legacies In Restorationmentioning
confidence: 99%
See 2 more Smart Citations
“…high nutrient availability) and biotic (i.e. low competitive pressure) ltering in abandoned croplands allows the establishment of weedy vegetation from the weed-contaminated soil seed bank [21,22,23] . Weed encroachment provides ecosystem disservices that can also affect the neighbouring natural habitats and agricultural elds.…”
Section: Introductionmentioning
confidence: 99%